2021
DOI: 10.1007/s00213-021-05860-5
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance to neurochemical and behavioral effects of the hallucinogen 25I-NBOMe

Abstract: Rationale 4-Iodo-2,5-dimethoxy-N-(2-methoxybenzyl)phenethylamine (25I-NBOMe) is a potent serotonin 5-HT2A/2C receptor agonist with hallucinogenic activity. There is no data on the 25I-NBOMe effect on brain neurotransmission and animal performance after chronic administration. Objectives We examined the effect of a 7-day treatment with 25I-NBOMe (0.3 mg/kg/day) on neurotransmitters’ release and rats’ behavior in comparison to acute dose. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 113 publications
2
14
0
Order By: Relevance
“…Extracellular DA and 5-HT levels were analyzed using an Ultimate 3000 System (Dionex, Sunnyvale, CA, USA), electrochemical detector Coulochem III (model 5300; ESA, Chelmsford, MA, USA) with a 5020 guard cell, a 5040 amperometric cell and a Hypersil Gold C18 analytical column (3 μm, 100 × 3 mm; Thermo Fisher Scientific, Sunnyvale, CA, USA). The details of the method have been described elsewhere [ 29 , 69 ]. The chromatographic data were processed by the Chromeleon v.6.80 (Dionex, Sunnyvale, CA, USA) software package run on a personal computer.…”
Section: Methodsmentioning
confidence: 99%
“…Extracellular DA and 5-HT levels were analyzed using an Ultimate 3000 System (Dionex, Sunnyvale, CA, USA), electrochemical detector Coulochem III (model 5300; ESA, Chelmsford, MA, USA) with a 5020 guard cell, a 5040 amperometric cell and a Hypersil Gold C18 analytical column (3 μm, 100 × 3 mm; Thermo Fisher Scientific, Sunnyvale, CA, USA). The details of the method have been described elsewhere [ 29 , 69 ]. The chromatographic data were processed by the Chromeleon v.6.80 (Dionex, Sunnyvale, CA, USA) software package run on a personal computer.…”
Section: Methodsmentioning
confidence: 99%
“…Our recent study confirmed the contribution of 5-HT 2A and 5-HT 2C receptors in effect on both brain neurotransmission and hallucinogenic activity in rats 9 . Moreover, the tolerance development in the neurotransmitters’ release and animals behavior was observed after 7-days treatment with 25I-NBOMe 10 . Due to their similar pharmacological effects on a human, NBOMe series were sold as LSD 11 .…”
Section: Introductionmentioning
confidence: 95%
“…Our results are in agreement with studies on drugs that promote serotonergic transmission as 3,4-methylenedioxymethamphetamine [MDMA; ( 42 )] or that act on the serotonergic receptor as 25I-NBOMe ( 37 ) and 2C-B ( 70 ) that induce a dispersive state that alters the visual and acoustic responses in rodents without affecting motor performance, especially at doses lower than 1 mg/kg. In contrast, some studies have shown opposite results, whereby doses of 25C- and 25I-NBOMe dose-dependent reduced locomotor activity in mice and rats ( 41 , 71 ). Therefore, LSD also interacts with several 5-HT (e.g., 5-HT 1A , 5-HT 2C , 5-HT 5 , and 5-HT 7 ) and DA (D 2l ike ) receptors [ Table 3 ; ( 58 ); Rickli).…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have also investigated the attenuated stimulant effect of LSD in the exploratory activity of mice lacking the 5HT 5A receptor, suggesting that this receptor subtype may be involved in the psychostimulant effect of LSD ( 72 , 73 ). Therefore, a study by Herian et al confirmed that 25I-NBOMe may have effects on short-term memory, locomotor function, and anxiety ( 71 ). In addition, studies on locomotion and exploratory activity in rats showed an increase in response following the administration of DOI similar to that induced by LSD, despite influencing more different receptors; consequently the mechanisms of action of DOI and LSD may not be identical ( 74 76 ).…”
Section: Discussionmentioning
confidence: 97%